2018
DOI: 10.3390/ijerph15112428
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Measles, Mumps and Rubella Vaccination among Somali Mothers in Stockholm

Abstract: Background: Vaccination hesitancy and skepticism among parents hinders progress in achieving full vaccination coverage. Swedish measles, mumps and rubella (MMR) vaccine coverage is high however some areas with low vaccination coverage risk outbreaks. This study aimed to explore factors influencing the decision of Somali parents living in the Rinkeby and Tensta districts of Stockholm, Sweden, on whether or not to vaccinate their children with the measles, mumps and rubella (MMR) vaccine. Method: Participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 25 publications
(27 reference statements)
2
46
0
Order By: Relevance
“…This Swedish study showed that acceptors followed immunization recommendations because they trusted experts [28]. Swedish parents with greater trust were more likely to vaccinate on time, dismiss MMR rumors, and ask more questions [25]. A questionnaire showed more acceptors and vaccine-hesitant parents in Italy considered their pediatrician to be competent, and to have spent enough time discussing MMR uptake, compared with rejectors [29].…”
Section: Healthcare Professionalsmentioning
confidence: 89%
See 4 more Smart Citations
“…This Swedish study showed that acceptors followed immunization recommendations because they trusted experts [28]. Swedish parents with greater trust were more likely to vaccinate on time, dismiss MMR rumors, and ask more questions [25]. A questionnaire showed more acceptors and vaccine-hesitant parents in Italy considered their pediatrician to be competent, and to have spent enough time discussing MMR uptake, compared with rejectors [29].…”
Section: Healthcare Professionalsmentioning
confidence: 89%
“…The most common reason for hesitancy or refusal was concern about adverse effects, revealed in 13 of 20 studies. This was mentioned by participants in relation to fear of autism in 10 studies [22][23][24][25][26][29][30][31][32][33] across three countries (UK, Italy, and Sweden). Rejectors and vaccine-hesitant parents were more likely to perceive adverse effects as highly probable and severe [29,34].…”
Section: Side Effectsmentioning
confidence: 99%
See 3 more Smart Citations